2011
DOI: 10.1007/s11412-011-9110-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of representational tools in collaborative and individual inquiry learning

Abstract: Constructing a representation in which students express their domain understanding can help them improve their knowledge. Many different representational formats can be used to express one's domain understanding (e.g., concept maps, textual summaries, mathematical equations). The format can direct students' attention to specific aspects of the subject matter. For example, creating a concept map can emphasize domain concepts and forming equations can stress arithmetical aspects. The focus of the current study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 80 publications
3
37
0
5
Order By: Relevance
“…The information and communications technology has virtually covered all professions and education fields, generating an impact in recent years that has led to reorganize the methodologies employed in the universities, as now new skills and competencies are required, and they affect educators (Kolloffel, Eysink & Jong, 2011). ICT contributes to improving teaching providing creativity and innovation, because through them we move from a process of learning that is a routine and even monotonous to a process full of novelty and dynamism.…”
Section: Discussionmentioning
confidence: 99%
“…The information and communications technology has virtually covered all professions and education fields, generating an impact in recent years that has led to reorganize the methodologies employed in the universities, as now new skills and competencies are required, and they affect educators (Kolloffel, Eysink & Jong, 2011). ICT contributes to improving teaching providing creativity and innovation, because through them we move from a process of learning that is a routine and even monotonous to a process full of novelty and dynamism.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also used self-reported data on the amount of time students spent using the system (e.g., García-Martín & García-Sánchez, 2013;Hsu & Ching, 2013;Romero & Barbera, 2011), and this approach raises an additional set of reliability challenges (Winne & Jamieson-Noel, 2002). Finally, in laboratory settings, Guo, Wang, Moore, Liu, and Chen (2009) and Kolloffel, Eysink, and Jong (2011) measured time-on-task as the difference between the start and the end of an experimental learning activity.…”
Section: Web Usage Mining In Distance Educationmentioning
confidence: 99%
“…However, to our knowledge, few studies have tried to compare the dyadic (face-to-face) and individual students' achievements in virtual environments designed for individual use. In this way, Kolloffel et al [4] have shown that collaborative learners outperform individuals regarding to a knowledge post-test after using environment with no special design for collaborative work. This result confirms that collaboration (even without special design for group work) fulfils a scaffolding function in learning and task solving.…”
Section: Collaborative Vs Individual Workmentioning
confidence: 99%